The Effectiveness of Storytelling on Decision-Making of Preschool Children - Dadashzade, Elahe; Ziaei, Mohammad Ali; Pourasad, Abdul-Hamid (Technium Social Sciences Journal, 2022)
Decision-making, as one of the cognitive processes, poses high importance in human life. This research aims to compare the effectiveness of storytelling and training on children's decision-making skills. In this study, 135 preschool girls were selected as multi-stage cluster sampling and randomly assigned into three groups: control group, training group, and storytelling. The research method was experimental, and its design was quasi-experimental, pre-test, and post-test. One-way variance and Tukey tests are utilized to analyze data, and the effect of teaching decision-making on children showed that the storytelling group's performance was higher than the training and control group. The results showed that storytelling has a significant effect on the decision-making skill of preschool students.